Why do patients with minor or moderate conditions that could be managed in other settings attend the emergency department?. Issue 6 (11th May 2011) - Penson, Robert; Coleman, Patricia; Mason, Suzanne; Nicholl, Jon
Abstract : Objectives: To estimate the potential of alternative providers of care for minor health problems to reduce demands on emergency departments (EDs). Methods: Data were collected in a type 1 urban ED over a 2-month period in two stages: questionnaire to adult attendees presenting to the ED; and a notes review. Results: The usable response rate was 68% (n=261/384). The notes review confirmed that more than two-thirds of the presenting conditions could have been managed in settings other than the ED. The attendees' reasons on the questionnaire indicated a strong belief that the only provider able to deal with their concerns at that time was the ED. For some users, the ED was not the first contact with a healthcare provider for the same health problem. Few believed that they would be seen quicker in the ED or that the ED was more convenient. The most frequent reason for presenting to the ED was 'being advised to attend by someone else'. The 'adviser' was more likely to be a health professional (doctor or nurse or NHS Direct) than to be 'friends or family'. Conclusions: Although there appears to be considerable potential for minor conditions to be managed in settings other than the ED, our findings indicate that patients will continue to present these conditions to the ED. Patient perceptions of the urgency of their treatment need, and also the availability and capacity of alternative services may be offsetting their potential to substitute for the ED. Advice from other services may be contributing to demands on the ED.